What are the main drivers of Brazilian income distribution changes in the new millennium? - Marcelo Cortes Neri (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
After three decades of persistently high income inequality, from 2001 Brazil experienced a downward inequality trend followed by rising household income growth. Both movements lasted until 2015. This work synthesizes the results of six papers, describing Brazilian income distribution trends and their close determinants. A common approach pursued looks jointly at inequality, mean, and social welfare growth rates. We use a vast array of data sets and empirical methodologies to fill the gaps found in the literature. Top incomes movements reduced income inequality fall but increased mean income growth, suggesting complex measurement and interpretation challenges. Overall, most of the inequality fall was driven by labour earnings, a channel dominated by firm-specific effects. Rising schooling and falling returns also played a key role, especially if parents' educational background is taken into account. Missing income values - or whether gross or disposable incomes concepts are used - did not affect inequality measures. Direct and indirect taxes increased inequality trends, while official monetary benefits did help, in particular conditional cash transfers. The Bolsa Familia programme was better targeted than all other transfers, most of which were linked to the Brazilian minimum wage.
Keywords: H22; I31; I38; C63; 330; income inequality; fiscal redistribution; top incomes; education premiums